KINERJA FAKTOR MAKRO EKONOMI DALAM MENDORONG PERTUMBUHAN DAERAH JAWA BARAT - Heri Hermawan; Dimas Bangun Sadewa (Jurnal Riset Ilmu Ekonomi, 2021)
Economic growth higlighted as a measurement of economic development within in area. The role of economic growth can explain how economy activity was work which supported by many kind of components in it.The purpose of this study is to examine supported economic growth components which are investment, government expenditure and labor force in West Java; 2000-2019. The study use data source from Bureau Statistic Centre (BPS), government expenditure by regional revenues and expenditures budget (APBD), and investment by gross domestic region product in 2000-20019. The result exlplains independent variables which investment, government expenditure and laborforce influence economic growth positively. Where independent variables describe the influence as 98% and 2% explains by other variable beside of model.